The term structure of interest rates, the expectations hypothesis and international financial integration: Evidence from Asian economies (2011)
The validity of the expectations hypothesis of the term structure is examined for a sample of Asian countries. A panel stationarity testing procedure is employed that addresses both structural breaks and cross-sectional dependence. Asian term structures are found to be stationary and supportive of the expectations hypothesis. Further analysis suggests that international financial integration is associated with interdependencies between domestic and foreign term structures insofar as cross-term structures based on differentials between domestic (foreign) short- and foreign (domestic) long-rates are also stationary. © 2010 Elsevier Inc.